Outer medullary circulatory defect in ischemic acute renal failure. - Yamamoto, K. (1984)
Changes in medullary circulation may contribute significantly to the pathogenesis of ischemic acute renal failure. The microcirculation of the outer medulla of the rat kidney was studied by morphometry, carbon injection, and scanning electron microscopy of vascular casts after temporary renal ischemia. Morphometry showed a markedly reduced vascular area and an increased tubular epithelial cell area in the outer stripe of the medulla 2 hours after blood reflow. Maximum diminution in vascular area occurred 24-48 hours after reflow, with swollen and later necrotic tubular epithelium compressing the surrounding vascular compartment. Outflow blockade of venous vasa recta in the outer stripe caused congestion of the inner stripe. Carbon injection and scanning electron microscopy of vascular casts confirmed the perfusion defects of the outer stripe. These results suggest that decreased blood reflow to the outer stripe of the medulla secondary to tubular epithelial cell swelling and necrosis plays a significant role in the pathogenesis of ischemic acute renal failure in the rat.